Asesmen Literasi Sains: Analisis Konseptual dan Implementasi bagi Calon Guru IPA - Gunawan, Gunawan; Zainuri, Baiq Nabila Saufika (Indonesian Publication Center, 2021)
This narrative review comprehensively examines the concepts and implementation of science literacy assessment for pre-service science teachers, synthesizing findings from various studies. Science literacy is recognized as an essential competency in science education, encompassing the understanding of scientific concepts, inquiry skills, and their application in daily life. Numerous studies highlight the importance of integrating science literacy into teacher education curricula, both at primary and secondary levels, as well as the role of teachers' beliefs in developing students' science literacy. This analysis sheds light on diverse assessment approaches, including the use of student worksheets, the integration of local wisdom, and the utilization of interactive multimedia. Challenges in implementing science literacy assessment are also identified, such as alignment with national curricula and the development of effective teacher professional models. The aim of this review is to provide a systematic overview of the conceptual framework of science literacy, the assessment methods employed, and their implications for enhancing the quality of pre-service science teachers, enabling them to foster science literacy competencies in their students.